Pengaruh Kinerja Keuangan dan Good Corporate Governance (GCG) Terhadap Nilai Perusahaan - Rolia Wahasusmiah (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This study aims to determine the effect of financial performance and good corporate governance (GCG) on the value of companies in manufacturing companies listed on the stock exchange Indonesia. The type of data used is secondary data in the form of annual report 2016. Population used in this study are all companies listed on the Indonesia Stock Exchange (BEI). This research uses purposive sampling method with total population of 144 companies and sample of 31 companies. The results show that simultaneously ROA, OPM, NPM, KM, and KI have a positive influence on firm value. While partially ROA have a positive influence on firm value. While OPM, NPM, KM, and KI have no positive influence on firm value).